2018
DOI: 10.1111/1467-9566.12808
|View full text |Cite
|
Sign up to set email alerts
|

(Un)contested evidence: scientific literature, systematic reviews and the politics of evidence in the introduction of HPV vaccines in Colombia

Abstract: This paper analyses the tensions between scientific literature and systematic reviews in the production of evidence in healthcare. Systematic reviews are devices developed - within evidence-based medicine - to navigate the complexities of scientific literature promising a clear and simple account of the knowledge on a particular issue. However, in practice, systematic reviews have a more complex relation with literature. Systematic reviews are shaped according to the interest of the local groups that produce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…This not only blurs the official boundary between reporting and conduct that has been carefully set up by the developers of reporting guidelines. Rather, it also exemplifies the importance of communicating the results of research for the overall process of scientific fact-making (see also Castañeda 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This not only blurs the official boundary between reporting and conduct that has been carefully set up by the developers of reporting guidelines. Rather, it also exemplifies the importance of communicating the results of research for the overall process of scientific fact-making (see also Castañeda 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Second, previous sociological research has questioned the straightforward narratives of bio‐scientific progress and preventive innovations in developing and diffusing the vaccine. By targeting the messy background of incorporating HPVV into national vaccine programmes, research has revealed the entanglement of bio‐medical research with economic, political and administrative rationales (Gottlieb, 2018; Maldonado Castañeda, 2019). Similarly, frictions and tensions in the implementation of vaccination policies and campaigns, discursive shifts in those campaigns and media‐driven public controversies around HPVV have been identified (Lindén, 2016, 2019; Mohr & Fredriksen, 2020).…”
Section: Findings Of Applied Health Research and Health Sociologymentioning
confidence: 99%
“…Terveyssosiologisille lähtökohdille rakentuvissa tutkimuksissa on ensinnäkin tarkasteltu rokotteiden vakiinnuttamista kansallisiin rokotusohjelmiin ja valotettu taloudellisten, tieteellisten, oikeudellisten ja poliittisen prosessien ja järkeilytyylien yhteenkietoutumisia näissä prosesseissa. Tutkimukset osoittavat, ettei rokotteita oteta käyttöön puhtaan lääketieteellisin kriteerein, eivätkä lääketieteelliset kriteerit ole ristiriidattomia (26)(27)(28)(29)(30). Toiseksi biopoliittisen hallinnan ja rokotteen sukupuolittuneisuuden aspektit on nostettu keskeisiksi.…”
Section: Katsaus Tutkimuskenttäänunclassified